The signal-to-noise ratio in bistable stochastic resonators - Imanbayeva, A.K.; Tokmyrzaeva, Zh.B. (Recent Contributions to Physics, 2017)
The most important parameter in any information transmission system is the signal-to-noise ratio (Signаl-to-Noise Rаtio or SNR). The signal level in this respect should be above the noise level. Recent studies have shown that in nonlinear dynamic systems, the effect of noise can lead to an increase in the signal-to-noise ratio. This phenomenon is called stochastic resonance. Stochastic resonance, whose study has grown to be a significant branch of noise research, is a rather general phenomenon wherein increasing the amount of input noise can optimise signal transfer in a system. To be more exact, we speak of stochastic resonance when the measure reflecting the quality of the transfer shows a maximum at non-zero input noise amplitude. In this paper we present the results of a numerical analysis of the stochastic resonance for a dynamical nonlinear system using the Duffing oscillator as an example. A numerical study was conducted in the MatLab.